Assessment of Surgical Antibiotic Prophylaxis in Pediatrics (ASAP-P). (4th October 2017) - Lombardi, Juliana; Nguy, Philippe; Ducharme, Antoine Robichaud; Thompson-Desormeaux, Félix; Ruo, Ni Nora; Girard, Gabrielle; Schnitzer, Mireille E; Thirion, Daniel; Papenburg, Jesse; Longpré, Audrey-Anne
Abstract: Background: No study to date has rigorously assessed the impact of interventions on improving surgical antibiotic prophylaxis (SAP) compliance in pediatrics. Our study is the first to adequately evaluate the timing criterion and to evaluate the persistence of compliance following the discontinuation of active interventions. Our objective was to assess the impact of a multifaceted intervention on improving pediatric SAP compliance in a hospital without an ongoing antimicrobial stewardship program. Methods: A multidisciplinary team consisting of clinical pharmacists and infectious disease physicians performed a series of interventions designed to improve pediatric SAP compliance in June 2015. A retrospective, quasi-experimental study was performed to assess SAP compliance prior to and following the interventions. Our study included patients under 18 years of age undergoing surgery in one of seven chosen surgical services (cardiac, urologic, orthopedic, neurologic, otorhinolaryngology, gastrointestinal and plastic surgery) between April and September 2013 (pre-intervention) and between April and September 2016 (post-intervention). A 10-week washout period was included in order to rigorously assess the persistence of compliance without ongoing interventions. SAP, when indicated, was qualified as non-compliant, partially compliant (adequate agent and timing) or totally compliant (adequate agent, dosing, timing, readministration and duration). Results: A total of 982 surgical cases requiring SAP were included in our primary analysis. The combined partial and total compliance increased from 51.4% to 55.8% (aOR 1.3; 95% CI, 1.0–1.8). Total compliance increased significantly from 29.0 to 38.3% (aOR 1.8; 95% CI, 1.3–2.4). Whereas improvement in correct dosing and readministration were significant, there was no significant improvement in correct timing. Compliance to agent selection and duration was already high. Conclusion: Our study demonstrated that overall SAP compliance did not significantly improve following a washout period, illustrating the importance of ongoing surveillance and feedback from an antimicrobial stewardship program. Our strict approach in evaluating the timing criterion may also explain the lack of a significant impact on overall SAP compliance. Disclosures: All authors: No reported disclosures.